The Model of the Conserved Epigenetic Regulation of Sex - Piferrer, Francesc; Anastasiadi, Dafni; Valdivieso, Alejandro; Sánchez-Baizán, Núria; Moraleda-Prados, Javier; Ribas, Laia (Frontiers in Genetics, 2019)
Epigenetics integrates genomic and environmental information to produce a given phenotype. Here, the model of Conserved Epigenetic Regulation of Sex (CERS) is discussed. This model is based on our knowledge on genes involved in sexual development and on epigenetic gene expression activation and silencing. This model was recently postulated to be applied to sexual development of fish and it states that epigenetic and gene expression patterns are more associated with the development of a particular gonadal phenotype, e.g., testis differentiation, rather than with the intrinsic or extrinsic causes that lead to the development of this phenotype. This requires the existence of genes with different possible epigenetic modifications, for example, changes in DNA methylation levels, associated with the development of a particular sex. Focusing on DNA methylation, the identification of CpGs the methylation of which is sex-linked constitutes the basis for the identification of Essential Epigenetic Markers (EEM), defined as the number and identity of informative epigenetic marks that are strictly necessary, albeit perhaps not sufficient, to bring about a specific, measurable, phenotype of interest. Here, we provide a summary of the genes where DNA methylation has been investigated so far, focusing on fish. We found that cyp19a1a and dmrt1, two key genes for ovary and testis development, respectively, consistently show an inverse relationship between their DNA methylation and gene expression levels, thus following CERS predictions. However, in foxl2a, a pro-female gene and amh, a pro-male gene, such relationship is not clear. The available data pertaining to other genes related to sexual development such as sox9, gsdf and amhr2 is also discussed. Next, we discuss the use of CERS to make testable predictions of how sex is epigenetically regulated and to better understand sexual development, as well as the use of EEMs as tools for the diagnosis and prognosis of sex. We argue that CERS can aid in focusing research on the epigenetic regulation of sexual development not only in fish but in vertebrates in general, particularly in reptiles with temperature sex-determination, and can be the basis for possible practical applications including sex control in aquaculture and also in conservation biology.